EFFECTIVENESS OF WARM GINGER WATER COMPRESSES IN REDUCING BACK PAIN IN 3RD TRIMESTER PREGNANT WOMEN IN THE WORKING AREA OF THE KABUN HEALTH CENTER - Herawati, Rika; Oktaria, Yofita; Andriana; Nurkhasanah, Siti (INTERNATIONAL JOURNAL OF MIDWIFERY AND BEAUTY, 2025)
Back pain disorder is always experienced by women in the Third Trimester. Introduction Back pain is the most common complaint with a prevalence rate of 49%. Based on ANC data from January until December 2022, there were 623 women in the third trimester of pregnancy, and 70% of women experienced back pain. There was a non-pharmacological effort from the working area of Kabun Health Center to reduce back pain in pregnant women. Warm ginger water compress is one of the non-pharmacological ways to reduce back pain. The study aims to investigate the effect of Warm ginger water compress on the intensity of back pain. This is Quantitative research with a quasi-experimental design with one group pretest-posttest 30 respondents were women in the third trimester of pregnancy in the working area of Kabun Health Center who were selected using purposive sampling. This research was conducted from January to June 2023. The study used observation/bio sheets and NRS on primary data and secondary data. The result of univariate analysis before giving Warm ginger water compress was 6,80 and after 2,80. The result of analysis using bivariate with Mann Whitney Test was p=0.00. It suggests that Ha was accepted, and Ho was rejected meaning that there was an effect on giving Warm ginger water compress to the intensity of back pain on the women in the third trimester of pregnancy in the working area of Kabun Health Center. It is expected that health workers especially midwives give Warm ginger water compress to pregnant women with back pain.